2015
DOI: 10.1123/jpah.2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Monitoring in Extremely Obese Adolescents From the Teen-LABORATORIES Study

Abstract: Background The accuracy of physical activity (PA) monitors to discriminate between PA, sedentary behavior, and non-wear in extremely obese (EO) adolescents is unknown. Methods Twenty-five subjects (9 male/16 female; age=16.5±2.0 y; BMI=51±8 kg/m2) wore three activity monitors (StepWatch [SAM], Actical [AC], Actiheart [AH]) during a 400 meter walk test (400MWT), two standardized PA bouts of varying duration, and one sedentary bout. Results For the 400MWT, percent error between observed and monitor recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Second, the inconsistency in PA measurements between the two methods must have resulted in errors in measuring PA. Accelerometers may underestimate upper body movements and movements involve few vertical motions like cycling, as the accelerometers were usually worn on the dominant hip of the participants [51]. Furthermore, studies have found that pedometers may not accurately record steps for people with abnormal gait patterns and people that are obese [53]. Pedometers also may not accurately capture activities in which the lower body is stationary (i.e., pushing, lifting, and carrying).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the inconsistency in PA measurements between the two methods must have resulted in errors in measuring PA. Accelerometers may underestimate upper body movements and movements involve few vertical motions like cycling, as the accelerometers were usually worn on the dominant hip of the participants [51]. Furthermore, studies have found that pedometers may not accurately record steps for people with abnormal gait patterns and people that are obese [53]. Pedometers also may not accurately capture activities in which the lower body is stationary (i.e., pushing, lifting, and carrying).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the accuracy and validity of physical activity measurement during a 400m walk test in youth with severe obesity. 28 Musculoskeletal pain complaints were documented during and after the completion of the 400m walk tests and consisted of knee, hip, calf, foot, and back pain along with numbness or tingling and leg cramps. Any of these indications during or after the test qualified as a musculoskeletal pain complaint and were combined for analysis (composite endpoint).…”
Section: Methodsmentioning
confidence: 99%